Specifics of turbo-alternator design with a high rotational speed of 6000 rpm - Boris A. Skvortsov (Krylov State Research Centre, 2021)
Object and purpose of research. The object under study is a 36 МW turbo-alternator (TA) with electromagnetic excitation and a high rotational speed of 6000 rpm, which can be used as an option for ac electric power source of 100 Hz in ship electric power systems with a turbo-alternator plant. The purpose is to perform electromagnetic calculations to deter-mine TA main data and technical characteristics, including the stator and rotor pack, their design, mass of active materials, etc. for comparison with a TA of the same power but 3000 rpm. Subject matter and methods. The studies are based on research and engineering data about investigations and design of double-pole industrial TA of 50 Hz as well as TA with a high current frequency (100 Hz and higher). For this purpose, the known formulas were used to estimate the size of TA active elements, excitation forces of stator and rotor windings, as well as methods for calculation of main TA parameters and technical characteristics. Main results. Design specifics of TA with a high rotational speed of 6000 rpm is identified, and results of electromagnetic estimations are obtained for a specific 36 MW turbo-alternator of 100 Hz with a forced close cycle cooling and better mass and size characteristics. Conclusion. The obtained results are of practical value, showing feasibility of developing a version of 36.0 МW TA with a rotational speed of 6000 rpm and significantly reduced specific mass and size characteristics – tentatively by 35–40% as compared to the existing TA of the same power but with a speed of 3000 rpm.